South Africa : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussions; and Statement by the Executive Director for South Africa. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that South Africa's economic performance has strengthened in the last several years, with real GDP growing by 5-5 1\2 percent in 2005-07, inflation declining to mid-single digits until recently, and employment growing steadily. However, 2008 saw a slowdown in activity, reflecting the cumulative impact of electricity power shortages, the global slowdown, and past monetary tightening. Executive Directors have welcomed the authorities' pursuit of a prudent fiscal policy, and their intention to maintain a broadly neutral fiscal stance in 2008.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet